2008
DOI: 10.1080/10888690801910567
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Positive Citizenship from Adolescence to Young Adulthood: The Effects of a Civic Context

Abstract: Researchers have theorized that programs to promote positive citizenship should begin with an opportunity for adolescents to participate in civic activities, such as community service or political volunteering. In this article we extend the theory by arguing that a more systemic approach is needed, in which a civic context is developed to promote citizenship. We hypothesize that living within a consistent civic context leads to civic engagement in late adolescence and into young adulthood. We use a diverse, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(146 citation statements)
references
References 41 publications
9
111
0
12
Order By: Relevance
“…For example, civic participation is related to having positive relationships with peers (Wentzel & McNamara, 1999;Yates & Youniss, 1998), and there is evidence that when youth feel a sense of solidarity with peers at school and believe that most students in their school display institutional pride in the school, they are more likely to commit to civic and political goals and values (Flanagan, et al, 1998). In addition, when youth believe that school, church and college are important in their friends' lives and that they can discuss issues and problems with their friends, they are more likely to participate civically in later life (Zaff, Malanchuk & Eccles, 2008). However, the amount of time spent in the evenings outside the home with friends is inversely related to civic knowledge in countries where peer group culture devalues education (Torney-Purta, 2002;Torney-Purta, et al, 2001).…”
Section: Social Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, civic participation is related to having positive relationships with peers (Wentzel & McNamara, 1999;Yates & Youniss, 1998), and there is evidence that when youth feel a sense of solidarity with peers at school and believe that most students in their school display institutional pride in the school, they are more likely to commit to civic and political goals and values (Flanagan, et al, 1998). In addition, when youth believe that school, church and college are important in their friends' lives and that they can discuss issues and problems with their friends, they are more likely to participate civically in later life (Zaff, Malanchuk & Eccles, 2008). However, the amount of time spent in the evenings outside the home with friends is inversely related to civic knowledge in countries where peer group culture devalues education (Torney-Purta, 2002;Torney-Purta, et al, 2001).…”
Section: Social Factorsmentioning
confidence: 99%
“…More recently, it has been found that involvement in formal groups (e.g., religious groups, sports groups, etc.) in which the individual is able to take on active and specific roles is related to prosocial-oriented civic participation (Albanesi, Cicognani & Zani, 2007), young people who belong to a club or team are much more likely to be involved in community service two years later (Hart, Atkins & Ford, 1998), people who have high levels of religious attendance and religious activity are more likely to be civically and politically active (Crystal & DeBell, 2002;Verba, et al, 1995;Youniss, McClellan, Su & Yates, 1999;Zaff, et al, 2008;Zukin, et al, 2006), and young people who participate in community-based organizations and in extra-curricular activities are more likely to participate both civically and politically in later life (Glanville, 1999;Otto, 1975;Verba, et al, 1995;Youniss, McClellan & Yates, 1997;Zaff, et al, 2008;Zaff, Moore, Papillo & Williams, 2003).…”
Section: Social Factorsmentioning
confidence: 99%
“…Alanyazında katılıma etki eden etmenleri araştırmaya yönelik birçok çalışma bulunmaktadır (Yates ve Youniss,1998;Flanagan, Faison, 2001;Albanesi, Cicognani, Zani, 2007;Zaff, Malanchuk, ve Eccles 2008;Hawkins, Letcher, Sanson, Smart ve Toumbourou, 2009 Açımlayıcı ve doğrulayıcı faktör analizi sonuçları siyasal ve toplumsal katılıma etki eden etmenleri ölçmek için geliştirilen bu ölçeğin Türk kültüründe geçerli ve güvenilir bir ölçme aracı olduğunu göstermiştir. Ölçeğin güvenirlik çalışması için iç tutarlılık katsayısı ile güvenirliğe bakılmıştır.…”
Section: Discussionunclassified
“…Diversity among Bi-ethnic students and differences in… 755 Stevens and Vollebergh 2008) and citizenship competences (Verkuyten and Martinovic 2006;Brug and Verkuyten 2007;Torney-Purta et al 2007;Zaff et al 2008;Geijsel et al 2012). Differences in cognitive outcomes between ethnic groups are usually explained by educational aspirations and expectations (Stevens et al 2011).…”
Section: Ethnic Composition Of the Familymentioning
confidence: 99%